Distribution of pore fungi (Aphyllophorales: Basidiomycotina) in the biotic units of Costa Rica - Carranza, Julieta (1996)
Two hundred and thirty-one species of pore fungi within 72 genera have been reported from Costa Rica. Based on Herrera and Gómez's 1993 Biotic Unit Map, the majority of the pore fungi are present in the Tropical-Tropical Unit (51 genera, 100 spp.), followed by Temperate-Tropical (46 gen. 85 spp.), Subtropical-Tropical (40 gen. 83 spp.) and Temperate-Cold (15 gen. 19 spp.). Only three genera are known from the Boreal-Tropical Unit. Many of these genera are cosmopolitan (45.8%), followed by 33.4% tropical and 20.8% boreal. Sixty-four cause white rot on hardwood trees and eight cause brown rot on hardwood and softwood trees. Amauroderma appears to be the gently genus restricted to a specific unit (Tropical-Tropical) and Fistulina and Bondarzewia to have a narrow host range (Quercus sp. and Alnus.).